Pregnancy impairs spatial memory and lowers mood. (16th November 2010) - Farrar, D; Marshall, KM; Neill, JC; Tuffnell, DJ
Abstract : Background: Female sex steroids are not only involved in reproduction, but influence the neurobiology of brain regions involved in memory processing. Sex steroid levels are substantially elevated in pregnancy. This investigation aimed to increase understanding of the influence of sex steroids on memory, attention and mood during pregnancy. Method: Pregnant participants were assessed each trimester and 3 months following birth. A non-pregnant control group were also included. A computer based assessment tool was used to assess memory and attention. Edinburgh Postnatal Depression Scale (EPDS) and General Health Questionnaire12 (GHQ12) scores were obtained and serum hormone estimation carried out. Ethics approval was obtained. Results: Group mean age, verbal intelligence and body mass index were comparable (n=47). The pregnant group showed a significantly reduced spatial recognition memory (SRM) mean percent correct score compared to the control group during the second (70% SD9 vs 82% SD12, p=0.001) and third trimester (73% SD9 vs 80% SD11, p=0.03) and at 3 months following birth (68% SD10 vs 80% SD10, p=0.0001). Pregnant group mean EPDS compared to the control group mean, was significantly greater in the first and second trimester and GHQ12 scores significantly greater in the first, second and third trimester. These effects did not persist following birth. Conclusion: Pregnancy seems to impair ability to remember previously seen spatial locations and this deficit remains evident at 3 months following birth. There were no significant correlations between SRM scores and sex steroids levels. Group EPDS and GHQ12 scores suggest lower mood only in pregnancy.